2016
DOI: 10.1038/s41598-016-0012-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of Cu(II)ATSM in human vascular smooth muscle cells and cardiomyocytes mediated by Nrf2 and DJ-1

Abstract: Cu(II)ATSM was developed as a hypoxia sensitive positron emission tomography agent. Recent reports have highlighted the neuroprotective properties of Cu(II)ATSM, yet there are no reports that it confers cardioprotection. We demonstrate that Cu(II)ATSM activates the redox-sensitive transcription factor Nrf2 in human coronary artery smooth muscle cells (HCASMC) and cardiac myocytes (HCM), leading to upregulation of antioxidant defense enzymes. Oral delivery of Cu(II)ATSM in mice induced expression of the Nrf2-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 61 publications
(98 reference statements)
3
42
0
2
Order By: Relevance
“…Many other Nrf2-inducing drugs are protective in animal models of Parkinson’s disease including triterpenoids (2-cyano-3-,12-dioxooleana-1,9(11)-dien-28-oic acid (CDDO) derivatives) [ 69 , 70 ], curcumin [ 56 , 71 ], 3H-1,2-dithiole-3-thione [ 72 ], carnosic acid [ 73 ] and resveratrol [ 74 , 75 , 76 , 77 ] (see [ 2 ] for further compounds). Cu II (atsm) provides protection in multiple mouse models of Parkinson’s disease [ 78 ], and has recently be shown to activate Nrf2 in mice [ 79 ]. Cu II (atsm) is currently under investigation in a phase 1 clinical trial in Parkinson’s disease patients, including efficacy secondary outcome measures (NCT03204929; Table 2 ).…”
Section: Parkinson’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Many other Nrf2-inducing drugs are protective in animal models of Parkinson’s disease including triterpenoids (2-cyano-3-,12-dioxooleana-1,9(11)-dien-28-oic acid (CDDO) derivatives) [ 69 , 70 ], curcumin [ 56 , 71 ], 3H-1,2-dithiole-3-thione [ 72 ], carnosic acid [ 73 ] and resveratrol [ 74 , 75 , 76 , 77 ] (see [ 2 ] for further compounds). Cu II (atsm) provides protection in multiple mouse models of Parkinson’s disease [ 78 ], and has recently be shown to activate Nrf2 in mice [ 79 ]. Cu II (atsm) is currently under investigation in a phase 1 clinical trial in Parkinson’s disease patients, including efficacy secondary outcome measures (NCT03204929; Table 2 ).…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Cu II (atsm) improves motor function and extends survival in multiple mouse models of amyotrophic lateral sclerosis, including when administered post-symptom onset [ 180 , 181 , 182 , 183 , 184 , 185 ], and has recently been shown to activate Nrf2 in mice [ 79 ]. Cu II (atsm) is currently being investigated in a phase 1 clinical trial (NCT02870634), and a linked phase 1/2 extension trial (NCT03136809) in amyotrophic lateral sclerosis patients, both with efficacy secondary outcome measures ( Table 2 ).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Cu II (atsm) has recently been shown to activate Nrf2 in heart (Srivastava et al, 2016), therefore Cu II (atsm) may be protective in PD models by activating Nrf2 in a copperdependent mechanism. These studies demonstrate that therapeutically increasing copper activates protective Nrf2 signalling.…”
Section: Copper Regulates Nrf2 Activationmentioning
confidence: 99%
“…62,68 Diacetyl-bis(N4-methylthiosemicarbazonato)copper(II) [Cu II ATSM] was reported to induce expression of antioxidant enzymes through activation of nrf2 and its co-activator protein DJ-1 in response to oxidative stress both in vitro and in vivo. 69 Recently, Newton et al developed a copper(II)-TSC complex NSC689534 with ROSinducing and GSH-depleting properties which was subjected to microarray analysis. 62 It was demonstrated that NSC689534 activated several ROS-connected pathways, including a number of genes involved in nrf2-mediated oxidative stress.…”
Section: Ros Induction and Activation Of Antioxidant Defensementioning
confidence: 99%